The last hope ebook - MacNeal, Susan Elia (Maggie Hope, 2024)
NATIONAL BESTSELLER • All will be revealed in this no-holds-barred finale of the Edgar Award–nominated Maggie Hope series as the intrepid spy teams up with fashion designer—and possible double agent—Coco Chanel to bring down the physicist behind Nazi Germany’s nuclear program. “Intrepid Maggie Hope’s high-stakes mission is fraught with danger and moral questions. . . . A heartfelt story.”—Cara Black, New York Times bestselling author of Three Hours in Paris Maggie Hope has come a long way since she was Mr. Churchill’s secretary. In the face of tremendous danger, she’s learned espionage, sabotage, and reconnaissance. But things are different now that she has so much to lose, including the possibility of a family with John Sterling, the man who’s long held her heart. British Intelligence has ordered Maggie to assassinate Werner Heisenberg, the physicist who may deliver a world-ending fission bomb for Germany. She’s shaken. An assassination is unlike anything she has ever done. How can the Allies even be sure Nazi Germany has a bomb? Determined to gather more information, Maggie travels to Madrid, where Heisenberg is visiting for a lecture. At the same time, couturier Coco Chanel, a spy in her own right with ambiguous loyalties, has requested a mysterious meeting with the British ambassador in Madrid—and has requested Maggie join them. As the two play a dangerous game of cat and mouse, Maggie tries to get a better understanding of Heisenberg, but is faced with betrayal and a threat more terrifying than losing her own life. Maggie desperately wants to find her happily-ever-after, but as the war reaches a fever pitch, the stakes keep rising. Now, more than ever, the choices she makes will reverberate around the globe, touching everyone she loves—with fateful implications for the future of the free world.